C. elegans-based screen identifies lysosome-damaging alkaloids that induce STAT3-dependent lysosomal cell death. Issue 12 (2nd April 2018) - Li, Yang; Zhang, Yu; Gan, Qiwen; Xu, Meng; Ding, Xiao; Tang, Guihua; Liang, Jingjing; Liu, Kai; Liu, Xuezhao; Wang, Xin; Guo, Lingli; Gao, Zhiyang; et al.
Abstract: Lysosomes are degradation and signaling centers within the cell, and their dysfunction impairs a wide variety of cellular processes. To understand the cellular effect of lysosome damage, we screened natural small-molecule compounds that induce lysosomal abnormality using Caenorhabditis elegans ( C . elegans ) as a model system. A group of vobasinyl-ibogan type bisindole alkaloids (ervachinines A–D) were identified that caused lysosome enlargement in C . elegans macrophage-like cells. Intriguingly, these compounds triggered cell death in the germ line independently of the canonical apoptosis pathway. In mammalian cells, ervachinines A–D induced lysosomal enlargement and damage, leading to leakage of cathepsin proteases, inhibition of autophagosome degradation and necrotic cell death. Further analysis revealed that this ervachinine-induced lysosome damage and lysosomal cell death depended on STAT3 signaling, but not RIP1 or RIP3 signaling. These findings suggest that lysosome-damaging compounds are promising reagents for dissecting signaling mechanisms underlying lysosome homeostasis and lysosome-related human disorders.